Review of Islamic Law on Customary Law Values in Community in North Lore Utara And Lore Peore, Poso-Indonesia - Hairuddin Cikka; Syaifullah MS (Fakultas Hukum, Universitas Warmadewa, 2024)
Long before state law, customary law was in effect, and no ordinary or customary law itself taught deviant behavior. Customs correct the wrong and provide solutions to social problems. The custom in the Pekurehua area is called the Pekurehua Tawailia custom, which is divided into the four largest divisions, namely the Posamboko custom/marriage, the mpogalo galo custom, or social order, the mpowia custom or farming methods, and the ngkapate custom or death. The reciprocal relationship between religion and custom creates a value that consists of several forms; namely, religion affects culture (tradition) in its formation, the value is religion. Still, the symbol is culture (custom). Religion can affect religious symbols; for example, Indonesian culture affects Islam, culture (tradition) can replace the value system and religious symbols. Religion and customs also have two similarities, namely both a value system and a symbol system.